REPRESENTASI ISU BUDAYA URBAN DALAM VIDEO GAME TROUBLEMAKER - Dwi Hapsoro, Rizki (Kartala, 2025)
Video game is a digital game that allows interaction between players and the computer. The advantage of video games lies in being an expressive medium that generates procedural experiences, creating a 'space of possibilities' that stimulates imagination, particularly in the context of urban culture. Urban culture is always linked to lifestyle and social disparities, especially regarding social violence in high schools. Video game Troublemaker was developed by the Gamecom Team, addressing urban cultural issues with a focus on social violence as the main content of the game. This research analyzes the narrative that represents urban cultural issues in the video game Troublemaker, as well as how the game creates tension for players. The goal is to identify representations in the narrative of urban cultural issues in the video game Troublemaker and understand the resulting tension. This study employs an interdisciplinary method, namely Roland Barthes' semiotics. The research findings indicate that the video game Troublemaker not only represents urban cultural issues as content but also provides a simulation as a seduction of tension. Keywords: Video game, Urban culture issues, Semiotics